Automated detection of radioisotopes from an aircraft platform by pattern recognition analysis of gamma-ray spectra. (December 2018) - Dess, Brian W.; Cardarelli, John; Thomas, Mark J.; Stapleton, Jeff; Kroutil, Robert T.; Miller, David; Curry, Timothy; Small, Gary W.
Abstract: A generalized methodology was developed for automating the detection of radioisotopes from gamma-ray spectra collected from an aircraft platform using sodium-iodide detectors. Employing data provided by the U.S Environmental Protection Agency Airborne Spectral Photometric Environmental Collection Technology (ASPECT) program, multivariate classification models based on nonparametric linear discriminant analysis were developed for application to spectra that were preprocessed through a combination of altitude-based scaling and digital filtering. Training sets of spectra for use in building classification models were assembled from a combination of background spectra collected in the field and synthesized spectra obtained by superimposing laboratory-collected spectra of target radioisotopes onto field backgrounds. This approach eliminated the need for field experimentation with radioactive sources for use in building classification models. Through a bi-Gaussian modeling procedure, the discriminant scores that served as the outputs from the classification models were related to associated confidence levels. This provided an easily interpreted result regarding the presence or absence of the signature of a specific radioisotope in each collected spectrum. Through the use of this approach, classifiers were built for cesium-137 ( 137 Cs) and cobalt-60 ( 60 Co), two radioisotopes that are of interest in airborne radiological monitoring applications. The optimized classifiers were tested with field data collected from a set of six geographically diverse sites, three of which contained either 137 Cs, 60 Co, or both. When the optimized classification models were applied, the overall percentages of correct classifications for spectra collected at these sites were 99.9 and 97.9% for the 60 Co and 137 Cs classifiers, respectively. Highlights: Automated detection of 137 Cs and 60 Co by airborne gamma-ray spectroscopy. Supervised pattern recognition of digitally filtered gamma-ray spectra. Methods development does not require field data of radioactive sources. Detection decisions supplied with % confidence for ease of interpretation. Methodology demonstrated with aerial surveys of six field sites.